Comparison of Brightness and Colour Characteristics of Mineral and Vegetable Oil-Based Offset Printing Ink - (:unkn) unknown (ASIAN JOURNAL OF CHEMISTRY, 2011)
Offset printing is a commonly used printing technique where the-inked image is transferred from a printing plate to a rubber blanket, then to the printing surface. The inks used in the offset process are made basically of a mixture of resins, vegetable or mineral oils, pigments and solvents. The use of vegetable Oil in the offset printing inks is gradually increasing each day, in terms of protecting environment and human health and print quality results. However, vegetable-based inks give good results in terms of print quality. The brightness of the inks printed on paper or Cardboard by offset printing are among the basic criterias of the quality. Gloss can also be a measure of the quality of a surface. The maximum colour tone of the CMYK process inks that could be depicted on colour picture printing is also among the basic quality criterias. In the study, mineral oil-based and vegetable oil-based inks were prepared specifically for the offset printing. Printing plates were prepared by being exposed with picture of ISO300 standard, specifically-prepared scale and CtP (computer to plate). Test printings were performed on two types of papers, matt and glossy-coated, which are frequently used in the production of printed goods in offset printing with mineral and vegetable oil-based inks with the help of a computer-controlled machine. In the process of printing, the printing was made with standardized parameters by measuring the values of L*a*b* by means of spectrophotometer. As a result of the measurements performed on the printed surface by glossmeter, it was determined that vegetable-based ink is more glossy than the mineral-based ink and that the only colour gamut it can simulate is broader.
Keywords: Printing ink; Brightness; Colour space; Offset printing